TANGGUNG JAWAB PEMERINTAH DAERAH DALAM PEMENUHAN HAK PENDIDIKAN ANAK PENYANDANG DISABILITAS DALAM PERSPEKTIF HAK ASASI MANUSIA - Triya Novitasari Haryono (JURNAL AKTA YUDISIA, 2025)
This study aims to explain and analyze the forms and implementation of the responsibility of the Government of North Kalimantan Province in fulfilling the right to education for children with disabilities from a human rights perspective. The research employs normative legal research using statutory and conceptual approaches. Legal materials were collected through library research, while the analysis was conducted using logical and systematic legal reasoning. The findings indicate that the responsibilities of the Government of North Kalimantan Province include the provision of special education services, facilitation of filial schools and learning spaces for areas outside public or private school zones, financial assistance, special quotas for underprivileged communities and zoning, provision of student dormitories and teachers’ housing, appropriate transportation facilities for special regions, supervision and evaluation, development of new schools and classrooms, construction of laboratories, and support for literacy programs and family education. However, the implementation of these responsibilities has not been optimal due to limitations in human resources, inadequate infrastructure, financial constraints, weak inter-agency coordination, and the absence of sanctions in North Kalimantan Provincial Regulation Number 6 of 2023 against educational institutions that fail to fulfill the right to education for children with disabilities.